PROJETO JÓIAS/COLARES COM REFERÊNCIA NA CULTURA GUARANI - ROSA, MONE M. D.; RODRIGUES, ELBRIO; HORSZCZARUK, DANIELA V.; GONÇALVES, GELSON; GOMES, SUELEN; FERREIRA, VITOR H. (Salão do Conhecimento, 2013)
Resumo